Role of Free Radicals on Retinitis Pigmentosa - Tumay, Mustafa; Hatungil, Rezan; Berkoz, Mehmet; Yalin, Serap; Erdogan, Semra (Asian Journal of Chemistry, 2012)
Retinitis pigmentosa is a retinal disease that leads to blindness. It has an unclear etiology and no known cure available in literature. The aim of this study is to study the role of free radicals on retinitis pigmentosa. This study was conducted on a test group composed of subjects who have been diagnosed with retinitis pigmentosa for ten years; and a control group of healthy individuals. To analyze the role of reactive oxygen products on retinal cell apoptosis, malondialdehyde (MDA) as a product of lipid peroxidation was measured. Also, to study the protectiveness of antioxidant enzymes over the retinal cells from apoptosis; activities pertaining to superoxide dismutase, catalase and glutathione peroxidase have been analyzed. The malondialdehyde values at the patient group have been found to be significantly higher than those at the control group. Antioxidant enzyme activities were found to be significantly lower in patient groups. Similar pattern of change was observed between patient and control group for all parameters in females and males. The malondialdehyde value was significantly higher and other parameters were lower in patient group according to controls. Results obtained from this research indicate that radical damage was high and antioxidant enzymes were low in retinitis pigmentosa. We may interpret these results to mean that exposure to free radical or antioxidant enzyme insufficiency may be some of the factors that trigger retinitis pigmentosa.